Development and Validation of the Turkish Spiritual Amnesia Scale (TSAS): Measuring Spiritual Disengagement Among Youth - Okan, Nesrullah; Kose, Nihat; Erol, Yusuf Celal; Sayin-Kilic, Mine (Springer, 2025)
The present study introduces the Turkish Spiritual Amnesia Scale (TSAS), a recently developed psychometric instrument intended to assess spiritual disengagement among Turkish youth. The theoretical framework underpinning the TSAS is predicated on the conceptualisation of spiritual amnesia as the progressive weakening of cognitive, emotional, and behavioural ties to spiritual beliefs and practices. This phenomenon is frequently precipitated by modernisation, digitalisation, and individualisation. The scale development process was guided by theoretical foundations such as Pargament's spiritual coping theory and Fowler's faith development theory. The process involved item generation, expert review, pilot testing, exploratory and confirmatory factor analyses, and reliability assessments. A total of 296 emerging adults participated in the EFA and 242 in the CFA. Additionally, criterion validity was assessed using a separate sample of 54 individuals. The findings obtained supported a unidimensional structure that explained 61.17% of the variance, with acceptable model fit indices (CFI = 0.911, RMSEA = 0.08). The TSAS demonstrated excellent internal consistency (Cronbach's alpha = 0.964) and robust test-retest reliability (r = 0.84, p < 0.001). The criterion validity of the scale was confirmed through a positive correlation with the Spiritual Contradiction Scale (r = 0.448, p < 0.001). The TSAS is a culturally grounded, theoretically sound, and psychometrically reliable instrument for the assessment of spiritual disengagement. Its application in psychological, spiritual, and sociocultural research has the potential to contribute to understanding contemporary forms of spiritual detachment in secularising contexts. Furthermore, the scale offers practical value for professionals working in youth counselling, spiritual assessment, and mental health services.
Keywords: Spiritual amnesia; Youth; Scale development; Spirituality; Cultural context; Turkey; Psychometrics